If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(3) + -1y = -18 Multiply 6 * 3 18 + -1y = -18 Solving 18 + -1y = -18 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + -18 + -1y = -18 + -18 Combine like terms: 18 + -18 = 0 0 + -1y = -18 + -18 -1y = -18 + -18 Combine like terms: -18 + -18 = -36 -1y = -36 Divide each side by '-1'. y = 36 Simplifying y = 36
| 2.4=02 | | a+1-2a-1E+1=2 | | y=3x+6x-9 | | 8x-15y=0 | | a+b-(ab)=1 | | 6(2)-y=-18 | | ba=a+b+1 | | 3(c+3)+8=-10 | | 2[x+9]=x+22 | | a+b+2=ba | | -5a+4+6a=10-19 | | -3(2x+1)+20=8x+5 | | 384-6x^2=0 | | 5=20a | | 7x-3x+9=29 | | -6x+17=8x+5 | | 5x-19=-7 | | 109-x=167 | | 3+5z= | | 6n-2=-68 | | -2.4k=42 | | b+5-6=18 | | 95+x=x | | 2x=-21+3 | | -0.54=.36m | | 195/200 | | 5+90=x | | 3x-30/18 | | -4-9=13-5x | | 24=4v | | -2/3(8x-9) | | -6(2s+6)= |